2018
DOI: 10.14359/51701294
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Assessment of T-Shaped Reinforced Concrete Squat Walls

Abstract: Reinforced concrete (RC) T-shaped walls have been studied by many researchers over the past decades due to their popularity. Among them, however, few investigations are conducted regarding T-shaped squat walls, especially for their seismic behaviors under nonprincipal bending action. To build the database and improve the understanding of structural walls, reversed cyclic tests of four RC T-shaped squat walls were conducted under displacement control. The variables were axial loads and lateral loading direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Before the selected modeling approaches were practiced in the parametric study, it was essential to validate these techniques by simulating some past experiments. Two H-shaped RC squat walls conducted by Ma and Li (2018) and two T-shaped RC squat walls conducted by Ma et al (2018) were selected for the validation, which were specimens HP0D0, HP5D0, TP5D0, and TP5D45. As illustrated in Figure 4, the web segment, 1300 mm in length, 1000 mm in height, and 100 mm in thickness, was reinforced with D10 deformed bars spaced at 150 mm as longitudinal reinforcement and R6 round bars spaced at 80 mm as horizontal reinforcement.…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the selected modeling approaches were practiced in the parametric study, it was essential to validate these techniques by simulating some past experiments. Two H-shaped RC squat walls conducted by Ma and Li (2018) and two T-shaped RC squat walls conducted by Ma et al (2018) were selected for the validation, which were specimens HP0D0, HP5D0, TP5D0, and TP5D45. As illustrated in Figure 4, the web segment, 1300 mm in length, 1000 mm in height, and 100 mm in thickness, was reinforced with D10 deformed bars spaced at 150 mm as longitudinal reinforcement and R6 round bars spaced at 80 mm as horizontal reinforcement.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Thus, during an earthquake, these walls are subjected to biaxial bending actions, and the contribution of different wall segments to the lateral strength could be rather complex. Experiments available in literature (Beyer et al, 2011; Brueggen, 2009; Ma et al, 2018; Ma and Li, 2018; Zhang and Li, 2016), solely provided information regarding loading direction 45° from the web. To further investigate the peak shear strength of non-rectangular RC squat walls under different lateral loading directions, finite element analyses (FEAs) are employed.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that when a T-shaped reinforced concrete (RC) shear wall is subjected to reciprocating loading, the load-bearing capacity of its flange wall in compression is much smaller than that of its web in compression. [11][12][13] Specifically, when the web is in compression, the strength of the T-shaped wall is jointly provided by the compressed concrete and reinforcement of the web, resulting in a high strength; when the flange is in compression, the concrete at the edge of the web cracks under tension and temporarily cannot bear the load, so the strength of the T-shaped wall is mainly provided by tensile reinforcement in the web, leading to a low strength. The strength asymmetry in the positive and negative directions leads to the situation that the strength design value of the T-shaped shear wall can only be set to the lower value of the two, analogous to the "short piece of wood" in the "cask effect."…”
Section: Introductionmentioning
confidence: 99%
“…[ 9–15 ] Previous tests also showed that the web was the weakest part of the flanged RC shear wall with ordinary strength stirrups, which usually failed with premature crushing of concrete in the free web boundary due to insufficient confinement. [ 16–19 ] To improve the seismic behaviors of flanged RC shear walls, we have designed flanged RC shear wall with high‐strength stirrups. The high‐strength stirrups serve to confine the concrete and postpone bucking of longitudinal rebars in the free web boundary, increasing the ductility of the walls simultaneously.…”
Section: Introductionmentioning
confidence: 99%